2015
DOI: 10.2147/prom.s86298
|View full text |Cite
|
Sign up to set email alerts
|

Developing a handheld record for patients with cystic fibrosis

Abstract: Patient handheld records (PHHRs) promote self-management and empower the holder to take a more active role in the management of their disease. They have been used successfully in improving preventative care for children and have contributed to improved adherence in a number of chronic illnesses. Despite the potential advantages, there are no standard PHHRs for patients with cystic fibrosis (CF). We report the consultation process that led to the development of a CF PHHR, describe the final document, and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This is in line with previous research that found My Medication Passport users wanted more space to add information that was relevant to them, for example, to record side effects. 18 In agreement with Narayan et al , 21 we found paper solutions to be more popular than digital, although some did prefer digital. Our finding that smartphone ownership can be a barrier is supported by Santo et al , 34 who found that 39% of 556 potential participants could not take part in a study of a medication reminder app, as they did not own a suitable smartphone.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous research that found My Medication Passport users wanted more space to add information that was relevant to them, for example, to record side effects. 18 In agreement with Narayan et al , 21 we found paper solutions to be more popular than digital, although some did prefer digital. Our finding that smartphone ownership can be a barrier is supported by Santo et al , 34 who found that 39% of 556 potential participants could not take part in a study of a medication reminder app, as they did not own a suitable smartphone.…”
Section: Discussionsupporting
confidence: 90%
“…in the context of CF 11,[31][32][33][34][35][36][37][38][39][40] (3rd session). Then the psychologist specialized in medication adherence (AD) presented a methodology for structuring the process of identifying solutions to the problems identified during the two focus group sessions (4th session).…”
mentioning
confidence: 99%